The influence of physical activity, diet, and lifestyle of patients on the course of polycystic ovary syndrome (PCOS) in women - Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Kmiotek, Weronika; Ragan, Dagmara; Oronowicz, Radosław; Staszczak, Paweł; Jaworska, Barbara; Długosz , Joanna; Bara, Maciej; Jama, Grzegorz (Quality in Sport, 2024)
Polycystic ovary syndrome (PCOS) is an endocrine disorder caused by multiple genetic and environmental factors, affecting women of reproductive age but extending across all stages of a woman’s life [1]. Major symptoms in many PCOS patients include menstrual cycle irregularities, difficulties in maintaining normal body weight, excessive body hair growth, acne, and fertility problems. The prevalence of PCOS varies depending on the definition used, ranging between 6-20%, making it the most common endocrine disorder among women of reproductive age [2,3]. It accounts for approximately 80% of cases of anovulatory infertility, disrupting various stages of the reproductive axis. Evidence from numerous studies suggests that lifestyle modification should be the first-line therapy for women with PCOS [4]. This paper focuses on research evaluating the treatment of this condition through lifestyle changes, physical activity, and diet. Such therapeutic interventions can significantly improve clinical outcomes and the health profile of PCOS patients by promoting favorable changes in body composition, partially normalizing sex hormone levels, reducing inflammatory parameters, and improving mental health. Therefore, the adoption of comprehensive lifestyle modifications is crucial in the treatment of polycystic ovary syndrome.